Analyzing digital video broadcasting terrestrial system using basic transmission model (Gaussian, Ricean and Rayleigh channel) / Siti Sabariah Salihin and Ros Shilawani S. Abdul Kadir - Salihin, Siti Sabariah; S. Abdul Kadir, Ros Shilawani
This paper analyzes the Digital Video Broadcasting - Terrestrial, DVB-T system. All basic transmission channel model (Gaussian, Ricean and Rayleigh) are examined. MATLAB techniques are presented with the transmission parameters setup. These parameters are bit error rate (BER) before Viterbi Decoder and after Viterbi Decoder, with varying Signal to Noise ratio (S/N ratio). The simulation results of actual DVB-T transmission and reception performance using 2K OFDM multi carrier with modulation level of 64 QAM using various transmission channel are graphically compared. These results are then compared to the theoretical value of DVB-T specification.